Influence of a powder feed rate on the properties of the plasma sprayed chromium carbide- 25% nickel chromium coating - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The plasma spray process is a leading technology of powder depositing in the production of coatings widely used in the aerospace industry for the protection of new parts and for the repair of worn ones. Cermet 75Cr3C2 - 25Ni(Cr) coatings based on Cr3C2 carbides are widely used to protect parts as they retain high values of hardness, strength and resistance to wear up to a temperature of 850°C. This paper discusses the influence of the parameters of the plasma spray deposition of 75Cr3C2 - 25Ni(Cr) powder on the structure and mechanical properties of the coating. The powder is deposited using plasma spraying at atmospheric pressure (APS). The plasma gas is He, which is an inert gas and does not react with the powder; it produces dense plasma with lower heat content and less incorporated ambient air in the plasma jet thus reducing temperature decomposition and decarburization of Cr3C2 carbide.. In this study, three groups of coatings were deposited with three different powder feed rates of: 30, 45 and 60 g/min. The coating with the best properties was deposited on the inlet flange parts of the turbo - jet engine TV2-117A to reduce the influence of vibrations and wear. The structures and the mechanical properties of 75Cr3C2 - 25Ni(Cr) coatings are analyzed in accordance with the Pratt & Whitney standard. Studies have shown that powder feed rates have an important influence on the mechanical properties and structures of 75Cr3C2 - 25Ni(Cr) coatings.